Choosing the composition of a drilling fluid containing partially hydrolyzed polyacrylamides (PHPA) for core drillings - Bülent Toka (Bulletin of the Mineral Research and Exploration)
In core (diamond) drilling operations, the controlling of drilling fluid’s rheological and filtration properties within specific value ranges is essential to ensure effective well cleaning and the maintenance of both mechanical and chemical equilibrium within the well. Furthermore, the additives in the fluid contribute significantly to improving core recovery efficiency. Partially hydrolyzed polyacrylamides (PHPA), known for their ability to encapsulate formations and drill cuttings to prevent the interaction of active clays with water, are also recognized for their effectiveness in improving core recovery efficiency. In core drilling operations, the high-speed rotation of the drill string can lead to challenges such as cake formation when the drilling fluid contains excessive solid particles (e.g., bentonite, calcite, barite, or drill cuttings). Drilling fluid engineers typically prefer polymer-based fluids with low solids content to reduce these issues. In this study, the rheologicaland filtration properties of various low-solids fluid compositions containing PHPA were investigated under laboratory conditions to identify the most suitable formulations for core drilling. The resultsof tests revealed that fluid compositions incorporating calcite + xanthan gum + modified starch + PHPA and bentonite + xanthan gum + modified starch + PHPA exhibited superior rheologicaland filtration properties compared to other fluid formulations. Additionally, the composition of PAC L + PHPA + calcium carbonate exhibited rheological and filtration values suitable for coredrilling applications.